The Correlation Between The Mastery of Vocabulary With The Ability In Listening of The Sixth Semester Students of English Department of FKIP UKI Toraja - Rachel Rachel (AgroSainT, 2012)
The objective of the research is to find out, the correlation between mastery of vocabulary and the ability in listening of English department students of FKIP UKI Toraja academic year 2009/2010. In this research the researcher applied descriptive method. The population of this research is the sixth semester students of English department of FKIP UKI Toraja academic year 2009/2010. The total of the population is 75 students. Because the population is relative large in number, the researcher applied random sampling to take out 20 students as sample. The instruments are used to collect data are the written test. It is used to find out the student’s mastery of vocabulary and the listening test is used to find out the ability in listening. The result of data analysis showed that there is a correlation between mastery of vocabulary and the ability in listening of the sixth semester students of English department students of FKIP UKI Toraja. This proved by the result of coefficient of correlation is 0.809. Based on the result above, it can be concluded that there is a significant correlation between mastery of vocabulary with the ability in listening of the sixth semester students of English department of FKIP UKI Toraja. It is shown by the point of coefficient of correlation is 0.809.